ANALISIS FAKTOR-FAKTOR KOMPENSASI PADA PT SUNGAI SEPUAH ESTATE (SSPE) KEC. BELITANG HULU KAB. SEKADAU: ANALISIS FAKTOR-FAKTOR KOMPENSASI PADA PT SUNGAI SEPUAH ESTATE (SSPE) KEC. BELITANG HULU KAB. SEKADAU - Aisyah; Makdalina (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2021)
This research was conducted with the aim of knowing the compensation factors at PT Sungai Sepuah Estate (SSPE) Belitang Hulu District, Sekadau Regency. This research is quantitative descriptive. The data collection technique used was in the form of a questionnaire distributed offline. The sample selected was 68 respondents based on the Slovin formula. The research method used is factor analysis using the KMO/MSA method. Based on the KMO/MSA value from factor analysis, the overall variables can still be predicted and can be analyzed further. Respondents' responses to compensation factors that were taken into consideration by PT Sungai Sepuah Estate (SSPE) in determining compensation, based on the overall results of the questions answered by respondents, it can be said that the compensation factors are very good through the average score of respondents' answers. The recommendation from the author as a company engaged in oil palm plantations is expected to conti nue to pay attention to the factors that are considered in providing compensation to employees. Keywords: Compensation Factors